Analisis Value For Money Anggaran Pendapatan Dan Belanja Daerah (APBD): Studi Pada Pemerintah Kabupaten Katingan Tahun 2018-2022 - Aldi Wiraguna; Yohanes Joni Pambelum; Golda Belladonna Umbing (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Finding out how the Regional Financial and Asset Management Agency of Katingan Regency measures financial performance using Value for Money is the goal. This research is categorized as a case study. Primary and secondary sources of information are used. A documentation is a data collector's best friend. We employ quantitative descriptive analysis to examine the data. In light of the fact that the Value for Money ratio level of program realization grew annually from 2018 to 2022, the study concludes that the fiscal performance of the Katingan Regency Government may be characterized as satisfactory. If we look at the economic ratio averaged over five years, we see that it falls at around 92.26%, thus we can say that it is economic. With an average efficiency ratio of little over 10%, this falls squarely into the "inefficient" group. The average effectiveness ratio is 97.93%, which falls into the effective group when it comes to efficacy. Economic efficiency and effectiveness meet the requirements set forth in Decree 600,900-327 of 1996, issued by the Minister of Home Affairs. Based on the data collected and analyzed from 2018 to 2022, the Katingan Regency Government has done an excellent job of overseeing the region's finances.